Administration, rhetoric, and climate policy in the Obama presidency. Issue 4 (7th March 2022) - Jones, Craig; Fowler, Luke
Abstract: Among the most well‐known traits of the Obama presidency are his rhetorical skills and reliance on administrative action to push forward policy in the face of an unresponsive Congress. This is particularly notable for climate change, where Obama used the tools of the administrative presidency to make policy and rhetoric to build public support for these actions. To this end, the authors examine how President Obama rhetorically constructed and rationalized his use of the Environmental Protection Agency to implement federal climate change regulations via the federal Clean Power Plan. The authors use a rhetorical analysis to examine President Obama's speeches from 2009 through 2015 that explicitly or implicitly reference climate change, greenhouse gases, and the Clean Power Plan, but also related topics, such as energy policy and climate agreements. The authors find that Obama relied on polysemy and the locus of irreparable in his speeches to sale the urgent need for administrative action on climate change. Conclusions suggest that the use of rhetoric and administrative action from the White House are key to how federal climate policy has been constructed in the U.S. 摘要: 巴马担任总统期间最著名的特征包括他的修辞技巧和在面临不响应的国会时依靠行政行动来推动政策。这在气候变化方面尤为明显，奥巴马在该问题上使用行政总统的一系列手段，制定政策和修辞来为这些行动建立公共支持。为此，作者分析了奥巴马总统如何从修辞角度对环境保护署的使用加以建构和合理化，以期通过联邦《清洁电力计划》执行联邦气候变化规制。作者使用修辞分析，检验了2009–2015年间奥巴马总统演讲，这些演讲直接或间接提到气候变化、温室气体、《清洁电力计划》、以及相关主题，例如能源政策和气候协议。作者发现，奥巴马在演讲中依靠一词多义和无法弥补的焦点问题来推动关于气候变化行政行动的迫切需求。结论暗示，对修辞的使用和白宫的行政行动在美国联邦气候政策建构过程中发挥了关键作用。. Abstract: Entre los rasgos más conocidos de la presidencia de Obama se encuentran sus habilidades retóricas y su confianza en la acción administrativa para impulsar la política frente a un Congreso que no responde. Esto es particularmente notable para el cambio climático, donde Obama usó las herramientas de la presidencia administrativa para formular políticas y retórica para generar apoyo público para estas acciones. Con este fin, los autores examinan cómo el presidente Obama construyó y racionalizó retóricamente su uso de la Agencia de Protección Ambiental para implementar las regulaciones federales sobre el cambio climático a través del Plan Federal de Energía Limpia. Los autores utilizan un análisis retórico para examinar los discursos del presidente Obama desde 2009 hasta 2015 que explícita o implícitamente hacen referencia al cambio climático, los gases de efecto invernadero y el Plan de Energía Limpia, pero también a temas relacionados, como la política energética y los acuerdos climáticos. Los autores encuentran que Obama se basó en la polisemia y el lugar de lo irreparable en sus discursos para vender la necesidad urgente de una acción administrativa sobre el cambio climático. Las conclusiones sugieren que el uso de la retórica y la acción administrativa de la Casa Blanca son clave en cómo se ha construido la política climática federal en los EE. UU.